2000
DOI: 10.1002/(sici)1098-2302(200005)36:4<325::aid-dev7>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

EEG correlates of the development of infant joint attention skills

Abstract: The development of the capacity for social attention coordination, or "joint attention," is a major milestone of infancy. Data from a recent study of handicapped infants have raised the hypothesis that the tendency to initiate bids for joint attention may reflect processes associated with the frontal cortex to a greater extent than other forms of infant attention coordination (R. Caplan et al., 1993). This hypothesis was examined in a longitudinal study of 32 normally developing infants. The results indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
178
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(206 citation statements)
references
References 48 publications
18
178
1
3
Order By: Relevance
“…It can be either initiated by the infant, calling an adult's attention to an object the infant is looking at, or the infant can follow the attention of an adult. It has been suggested that these two highly related skills are actually subserved by two different brain systems making the investigation of their development a very attractive project for cognitive neuroscience (Mundy et al, 2000;Mundy 2003).…”
Section: Joint Attentionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be either initiated by the infant, calling an adult's attention to an object the infant is looking at, or the infant can follow the attention of an adult. It has been suggested that these two highly related skills are actually subserved by two different brain systems making the investigation of their development a very attractive project for cognitive neuroscience (Mundy et al, 2000;Mundy 2003).…”
Section: Joint Attentionmentioning
confidence: 99%
“…This suggests that frontal lobe function may play a role in IJA. In addition, a longitudinal study of EEG coherence in infants from 14 to 18 months of age described EEG data suggesting left frontal and left and right central activation was associated with IJA ability at 14 and 18 months (Mundy et al, 2000). This finding was expanded upon by Henderson et al (2002) who used dense array electrodes for their EEG recordings and found medial frontal cortical activation in both hemispheres was associated with better IJA performance.…”
Section: Infant Electrophysiological and Functional Neuroimaging Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of these abilities requires the maturation of a complex set of brain areas, each of which can be associated with one or more of the three elements involved in social referencing. Frontal areas likely involved in the development of joint attention (Mundy, Card, & Fox, 2000;Mundy, Fox, & Card, 2003) are probably important for infants' developing ability to seek social information. Structures in the medial temporal lobe are important for recognition of emotions (Adolphs, Baron-Cohen, & Tranel, 2002;Cahill, Babinsky, Markowitsch, & McGaugh, 1995;Thomas et al, 2001), but to associate these emotions with novel objects also requires participation of medial temporal lobe areas involved in memory (Nelson, 1995).…”
mentioning
confidence: 99%
“…In case infants lost interest in the videos, brightly colored short video clips were presented as attention grabbers. This is an established procedure that allows to keep the infant's visual attention and to yield minimal eye and motor movements (e.g., Mundy et al, 2000;Paulus et al, 2014). Infants were videotaped during this procedure to be able to control for attentional distraction and movements.…”
Section: Materials and Proceduresmentioning
confidence: 99%